Abrogating GPT2 in triple‐negative breast cancer inhibits tumor growth and promotes autophagy. Issue 8 (9th January 2021) - Mitra, Devina; Vega‐Rubin‐de‐Celis, Silvia; Royla, Nadine; Bernhardt, Stephan; Wilhelm, Heike; Tarade, Nooraldeen; Poschet, Gernot; Buettner, Michael; Binenbaum, Ilona; Borgoni, Simone; Vetter, Martina; Kantelhardt, Eva Johanna; et al.
Abstract: Uncontrolled proliferation and altered metabolic reprogramming are hallmarks of cancer. Active glycolysis and glutaminolysis are characteristic features of these hallmarks and required for tumorigenesis. A fine balance between cancer metabolism and autophagy is a prerequisite of homeostasis within cancer cells. Here we show that glutamate pyruvate transaminase 2 (GPT2), which serves as a pivot between glycolysis and glutaminolysis, is highly upregulated in aggressive breast cancers, particularly the triple‐negative breast cancer subtype. Abrogation of this enzyme results in decreased tricarboxylic acid cycle intermediates, which promotes the rewiring of glucose carbon atoms and alterations in nutrient levels. Concordantly, loss of GPT2 results in an impairment of mechanistic target of rapamycin complex 1 activity as well as the induction of autophagy. Furthermore, in vivo xenograft studies have shown that autophagy induction correlates with decreased tumor growth and that markers of induced autophagy correlate with low GPT2 levels in patient samples. Taken together, these findings indicate that cancer cells have a close network between metabolic and nutrient sensing pathways necessary to sustain tumorigenesis and that aminotransferase reactions play an important role in maintaining this balance. Abstract : What's new? Glutamate pyruvate transaminase 2 (GPT2) serves a key role in glutaminolysis, a major feature of metabolic reprogramming in cancer, and is known to be upregulated in certain tumor types. In this study, GPT2 was found to be significantly upregulated in aggressive breast cancers, especially triple negative breast cancer (TNBC). Its downregulation, meanwhile, inhibited growth in triple‐negative MDA‐MB‐468 cells. In addition, GPT2 inhibition reduced cellular glutamate uptake, an effect linked to GPT2 modulation of the mTORC1 pathway and autophagy activity. The findings highlight relationships between metabolic enzymes, nutrient signaling and autophagy in breast cancer, potentially opening up new therapeutic opportunities.